1989
DOI: 10.1115/1.3240272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol and/or Methanol in Alcohol-Gasoline Blends on Exhaust Emissions

Abstract: The effect on exhaust gas emissions (carbon monoxide, CO, hydrocarbons, HC, and aldehydes, CHO) resulting from mixing methanol and/or ethanol with gasoline for automotive fuels has been studied experimentally. Tests were conducted on an OEM four-cylinder engine running at different conditions of equivalence ratio and spark timing. Fuel blends with different percentages of alcohol content and different ratios of methanol to ethanol in the alcohol mixture were tested. Results of this investigation indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…However, the same figure shows that increasing the ethanol percentage above 10% results in a decrease of the maximum pressure to a value even lower than that of pure unleaded gasoline. This may be explained as follows: the addition of ethanol to gasoline has two effects on the fuel blend properties; the first is an increase of the Octane number (see Table 1) since the latent heat of evaporation of ethanol is much greater than that of gasoline and, accordingly, ethanol addition helps to delay the chain reactions of the end gas (Bata and Roan, 1989); the second is a decrease in the heating value. It is to be noticed that these effects have opposite results in terms of engine performance.…”
Section: Resultsmentioning
confidence: 98%
“…However, the same figure shows that increasing the ethanol percentage above 10% results in a decrease of the maximum pressure to a value even lower than that of pure unleaded gasoline. This may be explained as follows: the addition of ethanol to gasoline has two effects on the fuel blend properties; the first is an increase of the Octane number (see Table 1) since the latent heat of evaporation of ethanol is much greater than that of gasoline and, accordingly, ethanol addition helps to delay the chain reactions of the end gas (Bata and Roan, 1989); the second is a decrease in the heating value. It is to be noticed that these effects have opposite results in terms of engine performance.…”
Section: Resultsmentioning
confidence: 98%
“…Palmer (1986) showed that 10% of ethanol addition to gasoline could reduce the concentration of CO emission up to 30%. Bata et al (1989) had tested different blend rates of ethanol gasoline fuels in engines, and found that the ethanol could reduce the CO and UHC emissions. Taylor et al (1996) used four alcohol fuels to blend with gasoline and concluded that adding ethanol can reduce CO, HC and NO emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Lower boiling point of alcohols also helps in attaining greater degree of combustion [11]. Some experimental studies measured the gasoline engine emissions fuelled with gasohols [6,9,10,12]. These studies however do not cover the measurement of unregulated emissions from these fuels.…”
Section: Introductionmentioning
confidence: 95%